Digital Tax Strategy Transformations Support National Competitiveness - Victoria Ari Palma Akadiati; Veronika Saptarini; Andy Fitriyadi Dharma Tilaar (International Journal of Economics, Commerce, and Management, 2025)
Digital transformation in the taxation system is one of the strategic steps of the Indonesian government in increasing administrative efficiency and state revenue. This study aims to analyze the form of digital tax strategy transformation in Indonesia, identify challenges and opportunities in its implementation, and assess its contribution to increasing national competitiveness. Based on literature studies and current policy analysis, it was found that tax digitalization shows progress through the implementation of e-filing, e-invoices, e-forms, and the imposition of Value Added Tax or VAT on digital services. Digitalization is still dominated by administrative aspects and has not fully touched on the strategic aspects of tax compliance. The challenges faced include low digital and tax literacy, limited technological infrastructure, and resistance from business actors, especially the informal sector and MSMEs. This study contributes to formulating policy recommendations to strengthen the implementation of a digital tax strategy that not only focuses on compliance, but is able to expand the tax base, increase fiscal efficiency, and create a fairer tax system that supports national competitiveness.